Ultrasound‐Driven On‐Demand Transient Triboelectric Nanogenerator for Subcutaneous Antibacterial Activity. Issue 3 (27th November 2022) - Imani, Iman M.; Kim, Bosung; Xiao, Xiao; Rubab, Najaf; Park, Byung‐Joon; Kim, Young‐Jun; Zhao, Pin; Kang, Minki; Kim, Sang‐Woo
Abstract: To prevent surgical site infection (SSI), which significantly increases the rate morbidity and mortality, eliminating microorganisms is prominent. Antimicrobial resistance is identified as a global health challenge. This work proposes a new strategy to eliminate microorganisms of deep tissue through electrical stimulation with an ultrasound (US)‐driven implantable, biodegradable, and vibrant triboelectric nanogenerator (IBV‐TENG). After a programmed lifetime, the IBV‐TENG can be eliminated by provoking the on‐demand device dissolution by controlling US intensity with no surgical removal of the device from the body. A voltage of ≈4 V and current of ≈22 µA generated from IBV‐TENG under ultrasound in vitro, confirming inactivating ≈100% of Staphylococcus aureus and ≈99% of Escherichia coli . Furthermore, ex vivo results show that IBV‐TENG implanted under porcine tissue successfully inactivates bacteria. This antibacterial technology is expected to be a countermeasure strategy against SSIs, increasing life expectancy and healthcare quality by preventing microorganisms of deep tissue. Abstract : A novel strategy of inhibiting microorganisms of deep soft tissue by electrical stimulation is presented through implantable, biodegradable, and vibrant triboelectric nanogenerator for being a potential treatment and prevention method of surgical site infection, especially against antimicrobial resistance, resulting in decreasing the morbidity and mortality rate of patients.